Penerapan Akad Ijarah Tanah Kas Desa Putat Tanggulangin Sidoarjo Untuk Meningkatkan Pendapatan Masyarakat - Lailatul Fitriani; Renny Oktafia (ITB AAS INDONESIA Surakarta, 2021)
Putat Village, Tanggulangin, Sidoarjo, a village that provides opportunities for the public in utilizing village treasures through a leasing system that is useful for seeking income. The purpose of this study was to find out how the application and impact of the village treasury Ijarah was carried out between the village and the Putat Village community to increase the income of the community using the Maqashid Sharia indicator. The method of this study uses kualitatif research using a case study approach, namely research carried out directly by using data collection techniques, namely observation, interviews, documentation. The results of this study are rent of village treasures in the implementation using the lottery system in this case in accordance with the pillars and requirements of Ijarah and Islamic Law, based on the Maqashid Sharia indicator consisting of religion, soul, reason, offspring, treasure, village cash tenants have the ability to increase income to meet daily needs so that it can change the condition of economy to be better.